Evidence-based sports medicine to prevent knee joint injury in triple jump - Wang, S.; Lyu, B. (Revista Brasileira de Medicina do Esporte, 2022)
Introduction: Triple jump has high technical requirements. However, in recent years, the frequent knee injuries during the training of triple jump athletes have seriously impacted their training and competition levels.